Suppression of runaway current generation by supersonic molecular beam injection during disruptions on J-TEXT. (5th June 2017) - Huang, D W; Chen, Z Y; Tong, R H; Yan, W; Wang, S Y; Wei, Y N; Ma, T K; Dai, A J; Wang, X L; Jiang, Z H; Yang, Z J; Zhuang, G; et al.
Abstract: The suppression of disruption-generated runaway electrons (REs) by supersonic molecular beam injection (SMBI) has been investigated on the J-TEXT tokamak. Experimental results demonstrate that the hydrogen injected by SMBI during plasma current flattop phase can provoke magnetic perturbations, which increase RE losses rapidly. The effective radial diffusion coefficient of REs due to SMBI is estimated as D r ≈ 16 m 2 s −1 . Based on this benefit, the SMBI has been used to explore the suppression of disruption-generated REs. In J-TEXT, RE current is created with rapid argon injection by a massive gas injection valve. It is found that hydrogen SMBI before disruption efficiently suppresses the generation of RE current.